Pendidikan adab di Kuttab Permata Qur’an Kartasura - Purnomo (Ta’dibuna: Jurnal Pendidikan Islam, 2023)
Kuttab is an alternative model of Islamic education that focuses on adab education. This research aims to find out the meaning of adab education for the Kuttab Permata Quran, the adab material taught, and how it is implemented. The research uses a descriptive-qualitative approach. The research subjects and informants were the initiators, managers, teachers, and guardians of the students. Data collection techniques include observation, interviews, and documentation. Checking the validity of the data using the source triangulation method. Miles and Huberman model data analysis techniques. This research shows that (1) the KPQ management believes that manners should not rely solely on social customs. KPQ is committed to integrating adab education into all teaching and learning activities, including teacher-guardian of student interactions. (2) The adab material taught includes adab towards Allah and the apostles, adab in assembly, adab towards parents, including teachers, and daily etiquette. (3) Punishment is permitted for cultivating adab. Adab is taught as a science in the subject of adab as well as an applied science in all subjects. Abstrak Kuttab adalah alternatif model pendidikan Islam yang berfokus pada pendidikan adab. Tujuan penelitian ini untuk mengetahui makna pendidikan adab bagi Kuttab Permata Quran, materi adab yang diajarkan, dan bagaimana implementasinya. Penelitian menggunakan pendekatan kualitatif deskriptif. Subjek dan informan penelitian adalah pemrakarsa, pengelola, guru, dan wali santri. Teknik pengumpulan data melalui observasi, wawancara dan dokumentasi. Pemeriksaan keabsahan data dengan metode triangulasi sumber dan teknik. Teknik analisis data model Miles dan Huberman. Penelitian ini menunjukkan bahwa (1) adanya keyakinan pengelola KPQ bahwa adab tidak boleh bersandar hanya pada kelaziman masyarakat. KPQ berkomitmen mengintegrasikan pendidikan adab pada seluruh kegiatan belajar mengajar, termasuk pada interaksi guru-wali santri (2) materi adab yang diajarkan meliputi adab kepada Allah dan rasul, adab bermajelis, adab kepada orang tua termasuk guru dan adab keseharian. (3) hukuman diperbolehkan dalam penanaman adab. Adab diajarkan sebagai sebuah ilmu dalam mata pelajaran adab sekaligus sebagai ilmu terapan dalam semua mata pelajaran.